Electrochromic nanopixels with optical duality for optical encryption applications - Ko Joo Hwan; Yeo Ji-Eun; Jeong Hyo Eun; Yoo Dong Eun; Lee Dong Wook; Oh Yeon-Wha; Jung Sanghee; Kang Il-Seok; Jeong Hyeon-Ho; Song Young Min (Nanophotonics, 2024)
Advances in nanophotonics have created numerous pathways for light–matter interactions in nanometer scale, enriched by physical and chemical mechanisms. Over the avenue, electrically tunable photonic response is highly desired for optical encryption, optical switch, and structural color display. However, the perceived obstacle, which lies in the energy-efficient tuning mechanism and/or its weak light–matter interaction, is treated as a barrier. Here, we introduce electrochromic nanopixels made of hybrid nanowires integrated with polyaniline (PANI). The device shows optical duality between two resonators: (i) surface plasmon polariton (SPP)-induced waveguide (wavelength-selective absorber) and (ii) ultrathin resonator (broadband absorber). With switching effect of between resonant modes, we achieve enhanced chromatic variation spanning from red to green and blue while operating at a sub-1-volt level, ensuring compatibility with the CMOS voltage range. This modulation is achieved by improving the light–matter interaction, effectively harnessing the intrinsic optical property transition of PANI from lossy to dielectric in response to the redox states. In our experimental approach, we successfully scaled up device fabrication to an 8-inch wafer, tailoring the nanowire array to different dimensions for optical information encryption. Demonstrating distinct chromaticity modulation, we achieve optical encryption of multiple data bits, up to 8 bits per unit cell. By capitalizing on the remarkable sensitivity to the angular dependence of the waveguiding mode, we further enhance the information capacity to an impressive 10 bits per unit cell.